Understanding glycolysis in Escherichia coli : a systems approach using nuclear magnetic resonance spectroscopy - Eicher, Johann Josef (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.